State of water and thermal properties of zinc and cobalt (II) phosphate solid solution - Antraptseva, N.M.; Solod, N.V. (Functional Materials, 2015)
It was established that the energy H-bonds and asymmetry of coordinationally connected of water molecules increases with elevation of cobalt content in the structure of Zn₃-xCox(PO₄)₂-4H₂O (0 < x≤1.00). Thermal properties of phosphate solid solution are investigated. It was found that their thermal stability correlate with the energy state of water molecules and has maximum in the phosphate with composition Zn₂Co(PO₄)₂·4H₂O. It was determined that the temperature ranges of formation and thermal stability of its partial and complete dehydration products at 30-40°C higher than in the phosphates, which has less cobalt content. The sequence of thermal solid phase transformations, which accompanying of Zn₃-xCox(PO₄)₂·4H₂O dehydration is established.